Brinquedos e brincadeiras nas telas de Portinari : um estudo sobre a infância lúdica contemporânea - Teixeira, Érica Jaqueline Pizapio (2015)
This research aims to recognize portrayed toys and games painter Candido Portinari on the screens in front of playful contemporary children of Colorado do Oeste, Rondônia. The colors of paints and poetic momentum of the playful context of art, Portinari features the kite, football, somersaults, swing, seesaw, the sieves, the doll, the top, the jump-meat, and diabolo, the marbles , the slingshot, the trap, among many other toys and games of his boyhood, or will be of our time, yet? It is an ambition that is revealed in identifying the playful timelessness of trifling life, depicted by the artist outside the context of the survey participants. Manson (2001), the playfulness of children in antiquity, it is with the various toys arising from the natural context, whether on the beach sand or in boizinhos made with vegetables. Timeless feature coupled to the object of this research which underlies in the qualitative method under the methodological mantle of ethnography, contemplating the analyzes on the screens of playful scenes of Portinari, opposite the meeting with the iconographic records in research. The empirical part of this study occurred with children 2 and 3 years of elementary school at the State School "Julieta Vilela Velozo" located in the municipality of Colorado do Oeste, Rondônia. In Part One, the researcher presents the trifling story of Candinho boy, the artist Portinari, which was marked by playful episodes in the first decade of the twentieth century, in the town of Brodowski São Paulo. A time when toys and games were made by the children themselves, with a repertoire of more varied. This statement, coming from the artist himself when narrates his playful done in the work "Brodowski Boys" and other works and poems. In Part Two, we present the theory under the retaining scholars as Huizinga (1938), who with his Homo Ludens, presents the game as primary element of human culture, with echo in categories of the game, presented in Caillois (1990). The play culture contemporary, in the real meaning of play with freedom of choice for those who perform any recreational activity, it is presented in the studies of Brougère, (2010) which describes relevant facts about the commercialization and industrialization of the toy. The game in addition to view the free sense takes place before the illusion and make-believe as essential by the imaginary factors, narrated by Château (1989). Relying still in that Party, Benjamin's studies (2009), Kishimoto (2010) and Gomes (2001), which strengthens the theoretical framework of the research. Part III presents the method adopted in the wake of ethnography that shown in iconographic analysis of the images in Portinari's paintings and photographs made from observations of play actions of the search field. Goes further, in the drawings made by the research participants and the collection brincantes information with the interview guide on the spot. Finally, in the fourth and final part, the search result is shown on the images of playful paintings of Portinari, recognition of toys and games in the contemporary world, elucidating the timeless concept of the game.